Repeated call sequences and behavioural context in long-finned pilot whales off Cape Breton, Nova Scotia, Canada. Issue 2 (4th May 2017) - Zwamborn, Elizabeth M. J.; Whitehead, Hal
Abstract: Repeated calls are part of the vocal repertoire of a diverse array of species, often presented in sequences that take time and effort on the part of the signal producer. Rhythmic repeated call sequences make up a significant portion of long-finned pilot whale ( Globicephala melas ) vocal production, yet the function of these sequences has not been investigated until now. In this study, we explored the relationship between behavioural context and the presence of these vocal sequences using recordings of a population of pilot whales found off Cape Breton, Nova Scotia, Canada. We used a binomial logit-link generalized linear model to look for possible predictors of the presence of repeated call sequences. They were more common in recordings of socializing whales than in those of whales in other behavioural states, and least common in resting whales. These vocal repetitions were also more common with larger group size. These results suggest that sequences function in maintaining contact and cohesion within this social species, possibly also serving in individual or group identification. The context of repeated call sequences indicate that they are not primarily mother–calf interactions, as they are heard just as commonly from groups without young. Future studies of pilot whale repeated call sequences should include individual-level behaviour and detailed acoustic calling context.